Kajian Etno-Semantik: Leksem Pengobatan dalam Budaya Osing Banyuwangi - Ashfiya, Ahmad Kavin; Hamidah, Latifah Winda; Fathullah, Azmi (Deskripsi Bahasa, 2026)
This study examines the semantic structure and cultural conceptualization of traditional medicinal lexicon in the Osing community of Banyuwangi. The research addresses two main questions: (1) how the componential structure distinguishes each medicinal lexeme, and (2) how cultural conceptualization is represented through these lexemes. Using a qualitative approach with an ethno-semantic method, data were collected through observation and in-depth interviews with native speakers. The analysis integrates lexical meaning, componential analysis, and cultural interpretation. The findings reveal that the Osing medicinal lexicon is organized into four primary subdomains: herbal remedies, physical treatment methods, ritual objects and media, and supernatural healing practices. Each subdomain demonstrates distinctive semantic components that reflect different modes of intervention, ranging from direct bodily manipulation to symbolic and spatial protection. Beyond lexical classification, the study shows that the Osing conceptualizes illness as a relational phenomenon involving the body, space, and non-physical entities. The body is understood as an open and manipulable space, while illness may originate from both physical and metaphysical sources. Consequently, healing practices integrate physical and ritual actions within a unified cultural system. These findings highlight that the medicinal lexicon not only encodes linguistic meaning but also represents a complex cultural model of health, emphasizing the role of ethno-semantics in uncovering local knowledge systems.